(untitled) (Revista Apotheke, 2022)
This research is the result of a workshop held in Early Childhood Education at the time I was a Master’s student in Teaching and Ethnic Racial Relations. Its objective is to provide the teaching of ethnic racial relations, highlighting the importance of black people in the construction of Brazilian society for students of Early Childhood Education from decolonial dialogues, using dialogic and expository methodologies. The theoretical framework included discussions about colonization, racism, racial identity. The methodological procedures adopted consisted of a workshop held in November to symbolize the month of Black Consciousness at the Joserinda Pereira School located in the municipality of Itacaré Bahia. The data obtained indicate the presence of racism and the absence of identity belonging. Racism has forms and structures and occurs due to the absence of a (de) colonial education. Based on the results and discussions presented, the importance of teaching for ethnic racial relations throughout the school year is considered, as well as the training of education and family professionals for ethnic racial relations.